Study on Land Use/Land Cover and NDVI Changes in Alliveru Watershed Project of West Godavari District, Andhra Pradesh Using Remote Sensing and Geographical Information System - Reddy, P. V. R. M.; Kona, S.; Reddy, B. J.; Reddy RV, S. K.; Ramana, R.V.; Rekha, D. V. S. R. L.; Ramaiah, N. S. (AMC Indian Journal of Civil Engineering, 2022)
Government of India has taken up Integrated Watershed Development Program (IWMP), now Pradhan Mantri Krishi Sinchayee Yojana (PMKSY) watersheds to restore the ecological balance by harnessing, conserving, and developing degraded natural resources such as soil, vegetation, and water in rainfed areas of the country. In Alliveru Project of Buttaigudem Mandal, West Godavari district of Andhra Pradesh, the watershed programme was started during 2013–2014 and completed in 2020–2021. The present study was taken up to assess the impact of watershed activities on LULC and NDVI using Remote Sensing and GIS techniques. Terrain corrected Resourcesat-2 LISS IV for year 2014–15 and 2020–2,1Erdas Imagine 2015, and ArcGIS 10.8 software have been used in the present study. Onscreen visual interpretation technique has been used while carrying out LULC change analysis and image processing has been used to generate NDVI images. NDVI analysis has shown increase in the vegetative cover in the project area. Significant changes were observed in LULC over the project implementation period due to the soil and water conservation activities by the State Level Nodal Agency (SLNA) under Panchayat Raj & Rural Development (PR&RD) Department. The results showed reduction in wastelands by 21.10% and increase in cropland and plantation by 4.47% and 6.36% respectively. Another positive indicator of watershed development in the project area is the increase in waterbodies by 43.88% due to construction of rain water harvesting structures , that is, 43 check dams, 44 percolation tanks, 6 farm ponds and 2 mini percolation tanks.